Effects of intralesional platelet-rich plasma in the patients with lateral epicondylitis of elbow (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
Lateral epicondylitis (tennis elbow) is a major cause of musculoskeletal pain involving common extensor origin of the forearm. This study was done to determine the effects of platelet-rich plasma on 15 patients with lateral epicondylitis. Selected patients were given intralesional platelet-rich plasma injection, activity of daily living instructions and paracetamol. Patients were assessed every 14 days interval by visual analogue scale, and the patient rated tennis elbow evaluation. Treatment response according to visual analogue scale and patient rated tennis elbow evaluation tool, the difference of improvement was found in respect to time, from pretreatment W1 (just before 1st Intervention) score to W11 score in every alternate week (p